Mode II delamination of carbon-glass fiber/epoxy hybrid composite under fatigue loading - Monticeli, Francisco Maciel [UNESP] (2022)
This work proposes a mechanistic model to evaluate and characterize the mode II delamination of carbon-glass/ fiber hybrid composites under fatigue loading. To this aim, crack growth was investigated at microscopic and macroscopic levels to measure the delamination propagation based on fracture mechanisms. The energy balance principle method described the energy release of the hybrid composite, evidencing greater energy available for fatigue delamination growth. The physics-based explanation for this enhancement is associated with the rougher fractured surface (tortuous propagation) due to the change in crack direction in the two reinforcements, stiffness synergy between the two fibers, and the silane coupling agent at the glass fiber surface. The proposed mecha-nistic model was used to analyze the physical-based behavior of the delamination of the hybrid and non-hybrid laminates, evidencing the contribution of each reinforcement to the SERR, with similar results at microscopic and macroscopic levels.